Assessment of adaptation strategies to flooding impacts in informal settlement : a case study in Yangon City, Myanmar - Khant Htoo Kyaw; Kim, Sohee Minsun; Vilas Nitivattananon; Pal, Indrajit; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Informal settlements are the feature of urbanization that is prominent in developing countries. They are mostly located in high-risk areas such as low-lying lands and on riverbanks. The higher number of lives have suffer from flooding as increasing number of settlements combined with the increasing rainfall due to changing climate. This research aimed to conduct an assessment for adaptation strategies to reduce the flood impacts in informal settlement. To achieve this, the study firstly analyze flood hazard, household condition, their adaptation strategies and perceptions. Subsequently, the study identifies livelihood vulnerability index of informal households. The access to condition and livelihood vulnerability was examined by 100 structured household interviews in two flood prone informal settlements in Yangon City. Then, adaptation assessment was carried out within the framework of Multi Criteria Analysis base on understanding oftheir situation and vulnerability. The key findings from this research illustrate that the urban poor in study areas have low adaptive capacity and high exposure and sensitivity as poor living in unplanned areas with limited access to livelihood capital due to inadequate support from city government have increased the vulnerability. The top ranking adaptation strategies form adaptation assessment were "subsidized for relocation ", "protect areas by dikes on long the side of river" and "enhanced hazard forecasting & early warning systems".
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Environmental Management
Thesis (M. Sc.) - Asian Institute of Technology, 2019
Keywords: Flood -- Myanmar -- Yangon; Flood control -- Myanmar -- Yangon; Squatter settlements -- Myanmar -- Yangon